PENGETAHUAN SIKAP DAN TINDAKAN PENDERITA TB PARU TERHADAP PENCEGAHAN KONTAK SERUMAH DI PUSKESMAS AIRTIRIS KECAMATAN KAMPAR KABUPATEN KAMPAR PROVINSI - Alvishenna Martin; Rohani Lamaria Simbolon; Tuti Restuastuti (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2016)
ABSTRACTTuberculosis (TB) is a pulmonary contagious infectious disease caused by Mycobacterium tuberculosis that attacks the lungs. The high level of pulmonary TB cases in Indonesia indicate that measure is necessary to decrease the rate of transmission. Transmission of pulmonary TB disease can be prevented if the patient had pulmonary TB good behavior towards prevention of the spread of pulmonary tuberculosis disease. Behavior is composed of three, namely knowledge, attitudes and measure. The purpose of this study was to determine the level of knowledge, attitudes and measure pulmonary TB patient to prevention household contacs in community health centers of Airtiris District Kampar Province Riau. The study was conducted in February-May 2015. Samples are 39 respondents pulmonary TB patients who have met the inclusion criteria. The instrument used was a questionnaire. The results showed that the respondents have a poor knowledge of as many as 25 people (64.1%) negative attitudes / not good as many as 28 people (28.2%) and measure quite as many as 20 people (51.3%).Keywords: Pulmonary tuberculosis, knowledge, attitude and preventive measures of pulmonary TB disease, pulmonary TB patients.